2016
DOI: 10.1007/s11207-016-0873-6
|View full text |Cite
|
Sign up to set email alerts
|

Photospheric and Coronal Observations of Abrupt Magnetic Restructuring in Two Flaring Active Regions

Abstract: For two major X-class flares observed by the Solar Dynamics Observatory (SDO) and the Solar TErrestrial RElations Observatory Ahead (STEREO-A) spacecraft when they were close to quadrature, we compare major, abrupt changes in the photospheric magnetic vector field to changes in the observed coronal magnetic structure during the two flares. The Lorentz force changes in strong photospheric fields within active regions are estimated from time series of SDO Helioseismic and Magnetic Imager (HMI) vector magnetogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
6
16
1
Order By: Relevance
“…This is similar to the previous reports of observed contraction events seen near disk center (e.g., Sun et al 2012;Gosain 2012;Simões et al 2013;Petrie 2016). Furthermore, the expansion for these loops is slower than the subsequent contraction, similarly as in the our observation (see also Figure 6b of Wang et al 2016) and other observations mentioned.…”
Section: Comparison Of the Model And Observationssupporting
confidence: 93%
See 1 more Smart Citation
“…This is similar to the previous reports of observed contraction events seen near disk center (e.g., Sun et al 2012;Gosain 2012;Simões et al 2013;Petrie 2016). Furthermore, the expansion for these loops is slower than the subsequent contraction, similarly as in the our observation (see also Figure 6b of Wang et al 2016) and other observations mentioned.…”
Section: Comparison Of the Model And Observationssupporting
confidence: 93%
“…Observational evidence suggests that while the contracting loop motions in flares are not common, they may happen at any phase of solar flares, including the early, impulsive, and gradual one (e.g., Liu et al 2012;Sun et al 2012;Gosain 2012;Simões et al 2013;Yan et al 2013;Shen et al 2014;Kushwaha et al 2015;Thalmann et al 2016;Petrie 2016). Gosain (2012) and Simões et al (2013) have shown that the onset of the contraction depends on the location of the loops with respect to the flare: loops located progressively further away from the flare contract later.…”
Section: Introductionmentioning
confidence: 99%
“…The authors40 noted that the sunspots may connect the two ends of the flux rope associated with the flare, and suggested that the decrease in the horizontal field of the sunspots could be explained by the elimination from the flux rope of some of the twist component of the field4142. In contrast to the previously studied case, the sunspot presented here was swept by the flare ribbon.…”
Section: Discussioncontrasting
confidence: 52%
“…As these peripheral loop contractions were always observed face-on and accompanied by eruptions from central magnetic structures (like a filament or an arcade eruption), the possibility could not be ruled out that apparent contraction is a projection effect due to the inclination of the loop plane pushed by the erupting structure, rather than a real contraction (from our survey experience, loop inclining is indeed more commonly observed when the loops are viewed with an edgeon state at the solar limb, and even some of them do not restore back to their original locations). As far as we know, only Petrie (2016) reported edge-on loop contractions in two active regions from the perspective of the Solar TErrestrial RElations Observatory (STEREO) in 195 Å, but due to the short interval of the process and the long cadence (∼5 minutes), the dynamics was not persistently revealed and not clear enough to be well studied. In addition, both the Petrie (2016) events show dramatic eruptions, but in this paper we also show a new type of loop contraction observed edge-on without violent eruptions.…”
Section: Introductionmentioning
confidence: 99%